Study on Water Shade Project and Its Importance In Haryana: Enhancing water productivity and sustainable horticulture in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In spite of the favorable conditions to growhorticultural crops throughout the year in Haryana production is restrictedbecause of water deficit. This is particularly noticeable during the dry season(December to June) when evaporation is higher than rainfall. Heavy rains inHaryana are concentrated in the wet season (July to August) and the averagerainfall in St Croix is 1041 mm per year which corresponds to 60% of the panevaporation. This water deficit can be ameliorated in the horticulture industryby growing crops under shady conditions. Plants require substantially lesswater (40% to 60%) because of reduced evapo-transpiration under shadeconditions. In addition, many tropical high value ornamentals perform better inshady conditions. This project proposes to develop a water budget forshade-house production of ornamentals. The specific objectives of this studyare: a) to determine the optimal WP of anthuriums by quantifying the shadingeffect on crop evapo-transpiration (ETc), growth and flower production; b) todetermine the crop coefficients that associates ETc under shade with panevaporation and potential evapo-transpiration (ETo); c) to estimate irrigationwater requirement throughout the year for anthurium cut flower production underoptimal shade conditions. A greenhouse with three shading levels (treatments)will be used for this study. Potted anthurium, a tropical ornamental cutflower, will be grown under each treatment and monitored for soil moisture andwater used. ETc, plant growth and cut flower yield will be evaluated todetermine the shading condition for optimal water productivity and waterrequirements. Climatic data (rain, relative humidity, pan evaporation, lightintensity, temperature, etc) from a weather station will be analyzed todetermine ETo. Water requirements under optimal growing conditions will beassociated with ETo and pan evaporation to determine crop coefficients. Theinformation obtained in this project will help horticulturists Haryana developdecision criteria for crop selection and adoption of a water-sustainableproduction system.